Key Characteristics of VR Videos and Their Impacts on Audience Engagement - Willson, Madeline (My University, 2025)
This content analysis of 300 YouTube VR videos took a quantitative approach to examine the impacts of genre, interactivity, storytelling richness, technical enhancement, technical disruption, and immersive audio on audience engagement. Previously, there have been few quantitative studies that have focused on more than one or two of these categories in relation to 360-degree videos. This study is one of the first to consider the impact of multiple categories on audience engagement solely for YouTube VR videos. Viewers are more engaged with VR videos that did not have technical disruption, as well as VR videos that had a higher level of storytelling richness. The impacts of genre, interactivity, technical enhancement, and immersive audio had no significant impact on audience engagement. This is consistent with previous studies as YouTube is significantly limited in regards to VR related features. Findings from the study contributed to the discussion on the technical behavioral aspect of human-to-content interactions, a part of the newly proposed audience engagement theory currently nested under the broader Uses and Gratifications framework. Future studies should consider using videos across the YouTube platform, as our study focused only on videos found on the YouTube VR channel.
Keywords: VR video; Audience engagement; Interactivity; Technical disruption; Immersion